2005
DOI: 10.1152/ajplung.00024.2004
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline and amorphous silica differentially regulate the cyclooxygenase-prostaglandin pathway in pulmonary fibroblasts: implications for pulmonary fibrosis

Abstract: Inhalation of crystalline (CS) and amorphous silica (AS) results in human pulmonary inflammation. However, silicosis develops only following CS exposure, and the pathogenic mechanisms are poorly understood. This report describes the differential abilities of CS and AS to directly upregulate the early inflammatory mediator COX-2, the recently identified prostaglandin E (PGE) synthase and the downstream mediator PGE 2 in primary human lung fibroblasts. Increased cyclooxygenase (COX)-2 gene transcription and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 39 publications
2
34
1
Order By: Relevance
“…In these experiments, primary human lung fibroblasts were treated with silica for 24 h, and Cox-2 expression was evaluated by Western blot and immunocytochemistry. We found that crystalline silica induced Cox-2 expression in a dose-dependent manner (O'Reilly et al 2005), and the arachidonic acid metabolism pathway was altered. Since both PGs and leukotrienes are relatively small molecules, a metabolomics study would yield valuable information on this pathway, which will be a focus of our future investigations.…”
Section: Discussionmentioning
confidence: 82%
“…In these experiments, primary human lung fibroblasts were treated with silica for 24 h, and Cox-2 expression was evaluated by Western blot and immunocytochemistry. We found that crystalline silica induced Cox-2 expression in a dose-dependent manner (O'Reilly et al 2005), and the arachidonic acid metabolism pathway was altered. Since both PGs and leukotrienes are relatively small molecules, a metabolomics study would yield valuable information on this pathway, which will be a focus of our future investigations.…”
Section: Discussionmentioning
confidence: 82%
“…[43][44][45] This study lends support to a relevant role of solubility and (non-)biopersistence in nonmalignant respiratory morbidity due to SAS, although it cannot be excluded that differences in particle size, shape, surface area, and direct or indirect cytotoxicity to target cells add to lower toxicity. 1,44,46 …”
Section: Discussionmentioning
confidence: 99%
“…There are two distinct types of silica found in nature, crys� talline and amorphous. The differential ability of amor� phous and crystalline silica to induce fibrosis is probably related to the physical and inflammatory properties of the silicas [16]. Several possibilities exist how silica induces fibrotic changes in the lungs.…”
Section: Silicosis In Four Brothers C a S E R E P O R T S Ijomeh 2009mentioning
confidence: 99%
“…However, silica dust may evoke the production of mediators which potentially cause fibroblast proliferation and increased matrix production even in the absence of inflammatory cells. Fibrosis leads to distortion of the normal lung ar� chitecture and disruption of the normal physiological pro� cesses of the lung [16,17]. Amorphous silica is more soluble and is more easily cleared from the lungs.…”
Section: Silicosis In Four Brothers C a S E R E P O R T S Ijomeh 2009mentioning
confidence: 99%
See 1 more Smart Citation